Getting to the heart of the matter: an investigation into captive great ape mortality and cardiovascular disease - Strong, Victoria J. (2017)
Great apes housed in zoological collections have an important role to play in conservation. A sound understanding about their health and welfare forms a critical part of their custodianship. Chapter 1 of this thesis outlines a systematic review of 189 published articles relating to the topic of great ape morbidity and mortality (Strong et al. 2016). It concluded that there was a critical need for an up-to-date review of zoo-housed great ape mortality, especially among the European population, to be carried out. Such a review of data relating to 681 great ape deaths was therefore performed and is outlined in Chapter 2 of this thesis. This mortality review identified the main causes of death within each taxa and age group, and allowed for a series of recommendations about future disease investigation and monitoring to be generated. Diseases of the cardiovascular system specifically, were identified as being associated with significant proportional mortality. Despite this, however, understanding about the epidemiology, pathogenesis and diagnosis of cardiovascular disorders among great apes remains poor. The remainder of the thesis therefore outlines a series of further projects and studies designed to confront this lack of knowledge and understanding: Chapter 3 focuses on cardiovascular disease epidemiology and identifies similarities and differences in disease risk between the taxa, highlighting age and male sex as potential risk factors. Chapter 4 is dedicated to the development of two protocols designed to standardise both the ante- and post-mortem investigation of cardiovascular disease in great apes. Chapter 5 addresses the controversial topic of carrying out cardiovascular disease screening in immobilised animals by comparing the effects of two anaesthetic protocols. Finally, Chapter 6 outlines a detailed study of great ape cardiovascular pathology and specifically idiopathic myocardial fibrosis in chimpanzees. The findings of each of the studies outlined in this thesis are informative, not only for the day-to-day management of zoo-housed great apes, but also for future research into their health, disease and therefore welfare.